Cutoff value for hypertrophic heart weight in the Japanese population. (February 2021) - Kakimoto, Yu; Asakura, Kumiko; Osawa, Motoki
Highlights: Heart weight grows with age until the age of 20 years and remains stable thereafter. Cutoff heart weight for cardiovascular death (CVD) is 407 g in men and 327 g in women, respectively. Cutoff heart weight/body height was 2.38 g/cm in men and 2.15 g/cm in women, respectively. Heart weight is a more useful predictor of CVD in men than in women. Heart weight is a better predictor of CVD than body mass index. Abstract: Background: Cardiac hypertrophy is a clinical risk factor for cardiovascular death (CVD) frequently recorded in autopsy reports, but the diagnostic criteria for the condition have not been clearly-established for autopsy. This study aimed to estimate the cutoff value for hypertrophic heart weight that can efficiently assist the postmortem diagnosis of CVD. Methods: We analyzed accumulated autopsy data from 3534 individuals aged 0–101 years. Results: We found that heart weight increased linearly with a person's age until 20 years, after which it remained stable. The mean heart weight in CVD cases was 473 g in men and 379 g in women. The mean heart weight in non-CVD cases was 385 g in men and 320 g in women. Receiver operating characteristic curve analysis for CVD assessment revealed that the cutoff value of heart weight was 407 g (odds ratio of 4.2) in men and 327 g (2.6) in women, and that of heart weight/body height was 2.38 g/cm (4.0) in men and 2.15 g/cm (2.6) in women, respectively. Overall, heart weight was a more useful predictor of CVD in men than in women. In logistic regression analysis, the predictive power of heart weight for CVD was higher than that of body mass index in both sexes. Conclusion: Thus, the criteria for hypertrophic heart weight are practical and useful for autopsy recordings, and it can be helpful for postmortem diagnosis of CVD. Our report is the first to reveal the cutoff value for hypertrophic heart weight in the Japanese population.